Low‐Dose Cu Ions Assisted by Mild Thermal Stimulus Inducing Bacterial Cuproptosis‐Like Death for Antibiosis and Biointegration - Xue, Yang; Zhang, Lan; Zhou, Jianhong; Chen, Jun; Ma, Yuwei; Han, Yong (Advanced functional materials, 2024)
Methicillin‐resistant Staphylococcus aureus (MRSA) is threatening human health due to its resistance to multiple antibiotics. Excessive copper (Cu) ions target the lipoylated proteins of tricarboxylic acid cycle of cancer cells, inducing proteotoxic stress and their cuproptosis death. Whether cuproptosis plays a part in killing MRSA by low‐dose supplement of Cu ions remains to be explored. Herein, Cu‐doped hydroxyapatite nanorods (PC) are prepared on polyetheretherketone (PEEK) to resist infection and improve PEEK performance in tissue integration with the assistance of near‐infrared (NIR) irradiation, and the mechanism against MRSA is elucidated. Mild photothermal stimulation increases bacterial membrane permeability, accelerating Cu ions’ intake and consequently inducing cuproptosis‐like death of MRSA. It is confirmed by aggregation of dihydrolipoamide S‐acetyltrans‐ferase (DLAT), deactivation of glutathione peroxides 4 (GPX4), and destabilization of Fe─S cluster proteins ferredoxin (FDX1) and lipoyl synthase (LIAS). Fortunately, fibroblast behaviors are upregulated on NIR‐irradiated PC. In vivo, PC with NIR irradiation exhibits outstanding MRSA elimination, reduced inflammation response, and improved biointegration. Overall, it is demonstrated that bacterial cuproptosis‐like death can be induced by Cu ions at a non‐cytotoxic dose when cooperated with mild heat stimulus, and this photothermal strategy of PC has greatly promising application in improving PEEK performance in clinic. To explore whether cuproptosis‐like death can be induced in MRSA at low‐dose Cu ions, Cu‐doped hydroxyapatite nanorods (PC) are prepared on polyetheretherketone (PEEK). PC with improved photothermal response and Cu release endows outstanding antibacterial activity and biointegration for PEEK, simultaneously. Mild photothermal stimulation by PC increases bacterial membrane permeability, accelerating Cu ions intake, and thus inducing cuproptosis‐like bacterial killing.